10.1016/s1544-8800(06)70733-3 (CrossRef Listing of Deleted DOIs, 2000)
AIM: To explore healthcare professionals' perspectives and experiences of patients with aborted cancer surgery. DESIGN: A multicentre study with a qualitative research design with focus group interviews according to Krueger and Casey. The study was guided by the Consolidated criteria for reporting qualitative research (COREQ) checklist. METHODS: Four focus groups were conducted, consisting of a diverse group of twelve healthcare professionals from three accredited comprehensive cancer centers and university hospitals. Data were collected in April-May 2025. A semi-structured interview guide was used to support the interviews. Data analysis was deductively analysed using directed content analysis guided by the Fundamentals of Care framework. RESULTS: The care context, its organization, culture and policies, makes it difficult to maintain safe person-centered care for patients undergoing aborted cancer surgery. The contact nurse plays an important role in upholding safe person-centered care despite these contextual barriers. Surprisingly, our findings showed that physical needs were entirely absent from the professionals' accounts. It was evident that nursing competence was underutilized in the care chain, particularly among the registered nurses on the ward. The need for supervision was clearly emphasized by all professional groups except the surgeons. CONCLUSIONS: Maintaining safe, person-centered care for patients undergoing aborted cancer surgery is hindered by organizational, cultural, and policy-related barriers within the care context. Despite these challenges, the contact nurse remains a key facilitator of person-centered care. IMPACT: What problem did the study address? The study addressed how organizational, cultural, and policy-related conditions within the care context make it difficult to maintain safe, person-centred care for patients undergoing aborted cancer surgery. What were the main findings? The contact nurse plays a crucial role in sustaining safety and person-centered care despite these contextual barriers. Where and on whom will the research have an impact? The research will impact healthcare organizations and multidisciplinary cancer teams by informing policy and practice aimed at strengthening person-centred and safe cancer care. PATIENT OR PUBLIC CONTRIBUTION: No patient or public involvement was required because the study focused on professional experiences, without involving patient data or issues affecting patients or the public.